Eksplorasi Kritis : Pengaruh Teori Positivisme dan Teori Kritis Dalam Pembentukan Kebijakan Publik Melalui Systematic Literature Review - Fariham Masula; Nurul Qurrotul Aini; Agung Winarno (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the influence of positivism and critical theory in the formation of public policy through the Systematic Literature Review (SLR) method. By reviewing relevant literature, this research explores how positivist and critical theory approaches can impact the decision-making process in public policy. The results of this SLR indicate that positivism provides an objective and measurable framework, while critical theory emphasizes normative and transformational aspects. This study concludes that the combination of these two approaches can produce more holistic and responsive public policies to the needs of society. These findings are expected to provide guidance for policymakers in adopting a more balanced and effective approach in shaping equitable and sustainable public policies